(untitled) (Revista Innova Educación, 2022)
The popularity of massively multiplayer online games such as Minecraft and Roblox has aroused the attention of teachers and educational researchers in the past decade. The purpose of this paper is to provide preliminary classroom experience using Roblox in game-based learning activities through action research. Convenience and quota sampling were used, intervening in four groups from different educational levels: 1 secondary, 1 high school, and 2 colleges. The learning activities with Roblox were conducted during the 2020-2021 academic year during the COVID-19 pandemic that forced Mexican schools to go digital. Roblox was used to learn content (like dinosaurs, contagious diseases, system definition) and interpersonal skills (negotiation, cooperation). The participants’ learning perception was explored through quantitative and qualitative data. Findings suggest that students enjoyed the Roblox learning activity as it allowed social interaction between classmates. The students evaluated the learning through the Roblox activity class on different scales (3,08; 3,18; 4,07 and 4,21 on the Likert scale). The results indicate that there are generational differences between groups. Finally, the paper offers concrete suggestions for the use of Roblox in the educational context.